PENGARUH PENDAPATAN DAN PENDIDIKAN KELUARGA TERHADAP PRESTASI BELAJAR IPS SISWA KELAS VII SMPN 4 DAYUN KAB. SIAK - Nisak, Khoirun; ', Gusnardi; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This research aims to understand the effect of family income, and education on learning acvhievement IPS seventh grade students of SMPN 4 Dayun District Siak. This research is a quantitative research, with amount of population is 72 students. This research is a census so that no sample and take the whole population as respondents. The method that used to gathering data is quisioner and documentation. Analysis data method uses descriptive analysis, multiple linier regression and classical assumption test. The result of the research shows there is influence simultaneously of family income and family education to the learning achievement with significance value of 0,000. Partially, family income has influence to the learning achievement with significance value of 0,000 and family education has influence to the learning achievement with significance of 0,000. With good family income and good family education, so that will increase learning ahievement.Keywords : Family Income, Family Education, Learning Achievement.